Agua, regadío y conflicto social en la provincia de León durante la Edad Moderna - Rubio Pérez, Laureano M. (Estudios humanísticos. Geografía, historia y arte, 1997)
The social struggle for water has marked the history of the villages of León, the provence of León being the provence with greater hydro resources. From the Midelle Ages to the s. XX León villages and their respective councils were in control of the water not only for human consumption but also for watering. Agriculture dependant on watering was developed during the Middle Ages, in the irrigated plain around the river Orbigo, which resulted in the construction of many dams and watering canals know as "zayas", "zequias" on "molderas". The defence of historical rights over water was one of the main commitments of the rural communities of León clown through its history.